Changes in Cultural Values of Ma'pasilaga Tedong (Case Study on Death Services in Lembang Sarambu, Buntu Pepasan District, North Toraja Regency - Ferdinand Kerebungu; Yoseph D. A. Santie; Siti Fathimah; Risma Sulle (Jurnal Mamangan, 2022)
This paper describes the socio-cultural changes that occur in the Lembang Sarambu community, Buntu Pepasan District, North Toraja, in the ma'pasilaga tedong tradition, along with the factors that influence the occurrence of these social changes. The method used in this research is the descriptive qualitative method, with data collection techniques of observation, interviews, and documentation. The results in this study are the values contained in the ma'pasilaga tedong tradition, namely 1) cultural values, ma'pasilaga tedong is a tradition that has been passed down from generation to generation to perfect the implementation of the rambu solo ceremony; 2) the value of customs, the Toraja people believe that the buffalo is a sacred animal; 3) moral values, in the ma'pasilaga tedong tradition, the buffalo that will be competed are buffalo that have certain criteria, such as the buffalo that will be competed must be the buffalo that will be sacrificed for the corpse; 4) social values, namely the tradition of ma'pasilaga tedong cannot be carried out if there is no solo sign ceremony'. The values that have changed in the ma'pasilaga tedong tradition are: 1) moral values, where the ma'pasilaga tedong tradition which originally aimed to comfort the bereaved family and as a form of empathy for the bereaved family has now become a gambling arena for ma'pasilaga tedong ; 2) and the initial social value of ma'pasilaga tedong was only done in one day, namely when there was a rambu solo' ceremony, but now it has been carried out for days even though the rambu solo' ceremony is not held. With the factor of cultural changes that occur caused by internal factors; population and discoveries and external factors; war and other cultural influences.